PERUBAHAN SOSIAL DI ERA MILENIAL DALAM PERSPEKTIF PENDIDIKAN ISLAM - Muhamad Hasan Taofik; Tutuk Ningsih (STKIP Subang, 2022)
This article discusses the significance and role of Islamic education in shifting social structures and functions of society. This study uses a library research approach, while this research is a type of qualitative research. The essence of education and the purpose of education in general is a system and means to improve the welfare of human life in all aspects. The fundamental question related to Islamic education and social change is about how Islamic education can simultaneously function as an agent of change and the dynamics of social change. It is a common understanding that Islam is a religion of love and peace, so it is only natural that Islam, a religion of mercy for all things, is also very concerned about the happiness and well-being of its people. Based on this statement, Islamic education is one of the best alternatives to build humanity, the findings of this study show that Islam builds society through education. The formation of a perfect human is the goal. Islamic education, which always considers two perspectives in all aspects external and spiritual, individual and social, as well as worldly and ukhrowi.